Deciphering gene mutations in the efficacy and toxicity of antineoplastic drugs: an oncology pharmacist’s perspective - Jiang, Yucai; Wen, Guolin Alexander (Frontiers in Pharmacology, 2025)
Background/ObjectivesThis article reviews some key emerging pharmacogenomic topics in oncology pharmacy practice.MethodsPublications selected to review were mainly sourced from the new drug approvals by the Food and Drug Administration and the new regimens listed in the National Comprehensive Cancer Network.ResultsKey pharmacogenomic topics were presented, including genetic alterations influencing drug metabolism, drug efficacy, and changes in therapeutic targeting; Relevant clinical updates and advancements were summarized to provide an in-depth understanding.ConclusionThe abundance of pharmacogenomic measures builds a solid foundation and heralds a paradigm shift toward individualized patient care.